IMPLEMENTATION OF PRAYERS FOR GUIDANCE AND COUNSELING STUDENTS - Elviana; Muslima; Nelisma, Yuliana (IKIP Siliwangi, 2024)
This research starts from the phenomenon that can be seen from the implementation shown by students, namely students who are still negligent in preparing for prayer, carrying out congregational prayers. This research aims to find out how high the level of prayer implementation of guidance and counseling students is. The research method that the author carried out was a quantitative method with a descriptive type. The population in this study was 101 students of guidance and counseling at UIN Sjech M.Djamil Djambek Bukittinggi class of 2021. The sampling technique used was total sampling. The data collection technique uses religious behavior instruments. Based on the results of this research, the author can conclude that the implementation of prayers for guidance and counseling students is as follows: 101 students of the Faculty of Tarbiyah Department of Guidance and Counseling class 2021 class A, B, C as many as 101 students performed prayers quite well, this can be seen from the data collection during research shows that overall student prayer implementation is still in the Medium category, and some are in the High and Very High categories. Based on the results of this research, it can be concluded that the better the student prayer implementation, the higher the student prayer implementation. Likewise, vice versa, the worse the performance of student prayers, the lower the performance of student prayers.